2008
DOI: 10.1002/pssc.200776817
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of commercial Gd2O2S:Tb phosphor

Abstract: The degradation of Gd2O2S:Tb phosphor was studied with Auger Electron Spectroscopy (AES) and Cathodoluminescence (CL). The surface reactions were monitored with AES while the light output was measured with a PC2000‐UV spectrometer. The CL of the Gd2O2S:Tb was excited with a 2 keV energy electron beam with a beam current density of 26 mA/cm2. The CL and AES were measured simultaneously while the sample was bombarded with the electrons in an oxygen atmosphere. A comparison between the low energy peaks of the AES… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…4,16 Gd 2 O 2 S:Pr phosphor powder finds application in X-ray microscope, soft X-ray phosphor screen for water window, and so forth. 17 On the other hand, Gd 2 O 2 S:Tb phosphor is widely used for display purposes in TV screens, CRT tubes, 18 and X-ray intensifying screens 19 due to its highly bright and efficient green emission under UV, cathode ray, and X-ray excitations. 20 Gd 2 O 2 S:Tb scintillator is useful in X-ray imaging and neutron radiography, 21,22 since it exhibits substantially better light output than the classic ZnS(Ag)/LiF material [21][22][23] by its much higher neutron capture cross-section and intrinsic conversion efficiency (~20%).…”
mentioning
confidence: 99%
“…4,16 Gd 2 O 2 S:Pr phosphor powder finds application in X-ray microscope, soft X-ray phosphor screen for water window, and so forth. 17 On the other hand, Gd 2 O 2 S:Tb phosphor is widely used for display purposes in TV screens, CRT tubes, 18 and X-ray intensifying screens 19 due to its highly bright and efficient green emission under UV, cathode ray, and X-ray excitations. 20 Gd 2 O 2 S:Tb scintillator is useful in X-ray imaging and neutron radiography, 21,22 since it exhibits substantially better light output than the classic ZnS(Ag)/LiF material [21][22][23] by its much higher neutron capture cross-section and intrinsic conversion efficiency (~20%).…”
mentioning
confidence: 99%
“…Sulfur in Gd 2 O 2 S is easily removed because of its high volatility. Dolo et al reported that the cathodoluminescence (CL) decreased after electron bombardment on the surface and the degradation in light intensity was caused by a new nonluminescent surface layer that formed due to the desorption of sulfur from the surface. It is difficult to maintain the original phase at high sintering temperature for 6 h, and thus, the sintering conditions must be carefully studied.…”
Section: Resultsmentioning
confidence: 99%
“…The trend of the S peak is not clear due to the influence of the Gd peak on the S peak. A linear least squares (LLS) method was previously applied to resolve the peaks for a similar study on the Gd 2 O 2 S:Tb 3+ powder [9]. It was shown that most of the S was also removed from the surface.…”
Section: Methodsmentioning
confidence: 99%